Recovery of the Decline in Activities of Daily Living After Hospitalization Through an Individualized Exercise Program: Secondary Analysis of a Randomized Clinical Trial - Garcia-Hermoso, A (Oxford University Press, 2021)
Background: During the period of hospitalization, patients can develop functional decline. The main aim of our study was to assess the natural trajectory of each activity of daily living (ADL) and to assess how in-hospital exercise could influence short-term trajectory of ADLs. Method: Acutely hospitalized patients (n = 297, 56.5% women) were randomly assigned to the intervention or control (usual care) group within the first 48 hours of admission. An exercise training program was prescribed in 2 daily sessions (morning and evening) of 20 minutes duration during 5-7 consecutive days for the intervention group. The primary endpoint was the change in every ADL (assessed with the Barthel Index) from 2 weeks before admission to hospital discharge. Results: Acute hospitalization per se led to significant in-patient s functional ability impairment in ADLs during hospitalization, whereas the exercise intervention reversed this trend (3.7 points; 95% CI: 0.5-6.8 points). After analyzing the trajectory of each one of the ADLs, patients in the control group significantly worsened all activities, but with a different degree of loss. For the between-group analysis, significant differences were obtained in many ADLs including bathing, dressing, grooming, bladder control, toilet use, transfers, mobility, and climbing stairs (p <. 05). The control group had the greatest impairment in all domains analyzed (ie, feeding, bathing, dressing, grooming, bowel control, bladder control, toilet use, transfers, mobility, and climbing stairs; p <. 05). Conclusions: An individualized multicomponent exercise training program in older adults is effective to reverse the loss of specific ADLs that frequently occurs during hospitalization. Each patient profile should receive an individualized prescription of exercise during hospitalizations. © 2021 The Author(s). Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved.